A framework for gamification of remote wrist rehabilitation exercises utilising non-invasive sensors - Khaksar, Siavash (2023)
After a soft tissue injury or surgery, patients often experience reduced muscle strength, flexibility, and pain in the affected area. This can create difficulties for them to perform simple daily activities such as eating, showering and employment activities. Engaging in rehabilitation exercises should help patients alleviate their symptoms and return to regular capabilities as well as sports and other recreational activities. Rehabilitation exercises need to be performed under a doctor’s or physiotherapist’s supervision to ensure it is safe and effective. However, the majority of people cannot attend local clinics regularly, and when the exercises are done at home, the supervisor cannot monitor the joint movements, the consistency of the exercise, or the strength requirements needed for the full rehabilitation. Additionally, frustration and losing motivation due to its repetitive nature and no clear goals are elements that make rehabilitation less effective.